Efficient Particle Transfer to Depth in Oxygen Minimum Zones of the Pacific and Indian Oceans - Weber, Thomas; Bianchi, Daniele (Frontiers in Earth Science, 2020)
The remineralization depth of sinking organic particles controls the efficiency of the biological carbon pump by setting the sequestration timescale of remineralized carbon in the ocean interior. Oxygen minimum zones (OMZs) have been identified as regions of elevated particle transfer and efficient carbon sequestration at depth, but direct measurements remain sparse in these regions and only provide snapshots of the particle flux. Here, we use remineralization tracers to reconstruct time-mean particle flux profiles in the OMZs of the Eastern Tropical Pacific and the Arabian Sea. Compared to the surrounding tropical waters, both OMZs exhibit slow flux attenuation between 100-1000m where suboxic waters reside, and sequester carbon beneath 1000m more than twice as efficiently. Using a mechanistic model of particle sinking, remineralization, and disaggregation, we show that three different mechanisms might explain the shape of the OMZ flux profiles: (i) a significant slow-down of remineralization when carbon oxidation transitions from aerobic to anaerobic respiration (e.g. denitrification); (ii) the exclusion of zooplankton that mediate disaggregation of large particles from suboxic waters (iii) the limitation of remineralization by the diffusive supply of oxidants (oxygen and nitrate) into large particles. We show that each mechanism leaves a unique signature in the size distribution of particles, suggesting that observations with optical instruments such as Underwater Vision Profilers hold great promise for understanding the drivers of efficient carbon transfer though suboxic water columns. In turn, this will allow more accurate prediction of future changes in carbon sequestration as the ocean loses oxygen in a warming climate.